On the presumption of equality - Räikkä J. (Routledge, 2022)
According to the presumption of equality, cases should be presumed to be similar when it is not known whether they are similar or different. When an allocative agent is unaware either of the appropriate distributive criterion or people’s relevant features (or both) and she cannot postpone the allocation, then she should distribute goods equally. I explore the nature and justification of the presumption of equality and bring out how commentators have confused it with the claim that all people are relevantly similar and therefore deserve similar treatment, unless there is a specific reason for different treatment. The claim of prima facie equality concerns substantive criteria of justice and should not be confused with the presumption of equality. I will also argue that in some cases, an allocative agent can easily justify the use of the presumption of equality and equal distribution by referring to the relative costs of potential errors. However, I conclude with a discussion of the overall significance of the presumption of equality by considering cases that reveal some important limitations on its use.